# Solve the following simultaneous equations. 3x + 2y = 6, 18x + y = 9

justaguide | Certified Educator

calendarEducator since 2010

starTop subjects are Math, Science, and Business

We have to solve the following set of simultaneous equations:

3x + 2y = 6 ...(1)

18x + y = 9 ...(2)

6*(1) - (2)

=> 18x + 12y - 18x - y = 36 - 9

=> 11y = 27

=> y = 27/11

substitute in (2)

18x + 27/11 = 9

=> 18x = 9 - 27/11

=> 18x = 72/11

=> x = 4/11

We get x = 4/11 and y = 27/11

check Approved by eNotes Editorial

## Related Questions

giorgiana1976 | Student

We'll solve the system using substitution, instead elimination.

We'll change the 2nd equation into:

y = 9 - 18x

3x + 2(9 - 18x) = 6

We'll remove the brackets:

3x + 18 - 36x = 6

We'll combine like terms:

-33x = 6-18

-33x = -12

We'll divide by -3:

11x = 4

x = 4/11

We'll substitute the value of x into:

y = 9 - 18x

y = 9 - 18*4/11

y = (99 - 72)/11

y = 27/11

The solution of the system is represented by (4/11 ; 27/11).

check Approved by eNotes Editorial